KIAT EDUKASI SIMULASI MANAJEMEN PENANGANAN AWAL EPISTAKSIS PADA REMAJA - Arianti, Linda; Widayati, Dhina; Setyorini, Dwi; Arian Chumaini Hidayatullah (STIKES dan AKZI Karya Husada Kediri, 2024)
Abstract Epistaxis is one of the emergencies in the field of ENT (ear nose throat), that is most often found in the community, including in the school environment. Students need to know the initial management of epistaxis so they can handle it well. The aim of this service activity is to provide management education for the initial treatment of epistaxis through simulation. The method for implementing this activity is through education and simulation involving 25 students who are members of the PMR SMK Cahnda Bhirawa Pare. The service activities were carried out in 3 sessions, namely: counseling about epistaxis, counseling on how to provide first aid for epistaxis and a simulation of how to provide first aid to individuals experiencing epistaxis. The result of this community service activity was that there was an increase in students' knowledge and ability in providing first aid to individuals experiencing epistaxis, namely from almost all (44%) in the poor category (before the activity) to almost all (92%) in the good category. Education using a simulation approach can increase students' understanding of first aid management for epistaxis cases so they are able to provide first aid appropriately. The education method using a simulation approach can be used as a medium for conveying information in the management of initial treatment of epistaxis in students who are in the adolescent group. Keywords: education, simulation, management, epistaxis